The struggle of T. M. Hasan in government building Republic of Indonesia in Sumatra (1945-1948) - Suprayitno, ,; Abd Aziz, Mohd Kasturi Nor (2014)
The period of revolution for independence in Sumatra still be a sexy topics in the study of contemporary history of Indonesia. This crucial period sufficient to record a lot of memory about the story of the main character of the foundation stone of the government of the Republic in Sumatra. Figure of Mr. TM Hasan, that can defuse political tension, when the struggle for independence took place in the full of conflict and turmoil. No wonder the Japanese military leaders, and the Allies needed his help to defuse the situation in the city of Medan at the time. Attitudes and lines such struggle has led to Mr. T. M. Hasan became the figure of a leader who was instrumental in building the basics of the Government of the Republic of Indonesia in Sumatra with the wise. Because of that attitude and act of the struggle made him a symbol and role model worthy of the nation's current leaders and society in general.